PEMBERDAYAAN SISWA DALAM PENANGANAN CEDERA MUSKULOSKLETAL MELALUI PEMANFAATAN E-FA (EDUCATION FIRST AID) GAME - Eky Madyaning Nastiti; Feri Ekaprasetia; Rida Darotin (JPMK : Jurnal Pengabdian Masyarakat Kasih Published by Unit Penelitian dan Pengabdian Kepada Masyarakat (UPPM) STIKES Dirgahayu Samarinda, 2023)
Musculoskeletal injuries, such as sprains, are one of the injuries that often occur in schoolchildren. This is due to a lack of information and understanding regarding first aid for injuries. Therefore, educational efforts are needed along with technological developments in order to empower students. The purpose of this service activity is to provide education to students through digital games containing the concept of first aid for musculoskeletal injuries (E-Fa Game). The method used is in the form of a pretest, providing health education using the E-Fa Game, and re-evaluating with a post-test. The results of this community service show that 83% of participants understand the procedures for first aid for extremity injuries, including resting the injured area (rest), giving ice, bandaging (compression), and elevating the injured area (elevation). Through this community service activity, it is hoped that more and more students will understand the procedures for first aid for musculoskeletal injuries, so that they will be able to become laypersons who are able to provide help in cases of injuries that occur around them.